2016
DOI: 10.1177/0363546515624916
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of Stress Distribution Patterns in Symptomatic Valgus Instability of the Elbow in Baseball Players

Abstract: The information obtained from the CT images can useful for early detection of overstress conditions of the elbow joint.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 26 publications
0
38
0
Order By: Relevance
“…The high-density area (HDA) was defined as the upper one-third of the entire range, from the minimum to the maximum HU, in each individual ankle. 7 The proximal ankle joint surface was divided into 5 parts as follows: anterolateral part of the tibia (AL-Ti), anteromedial part of the tibia (AM-Ti), posterolateral part of the tibia (PL-Ti), posteromedial part of the tibia (PM-Ti), and the fibula. The distal ankle joint surface was divided into the following 4 parts: anterolateral part of the talus (AL-Ta), anteromedial part of the talus (AM-Ta), posterolateral part of the talus (PL-Ta), and posteromedial part of the talus (PM-Ta) ( Figure 1A).…”
Section: Quantitative Analysis Of the Mapping Imagesmentioning
confidence: 99%
“…The high-density area (HDA) was defined as the upper one-third of the entire range, from the minimum to the maximum HU, in each individual ankle. 7 The proximal ankle joint surface was divided into 5 parts as follows: anterolateral part of the tibia (AL-Ti), anteromedial part of the tibia (AM-Ti), posterolateral part of the tibia (PL-Ti), posteromedial part of the tibia (PM-Ti), and the fibula. The distal ankle joint surface was divided into the following 4 parts: anterolateral part of the talus (AL-Ta), anteromedial part of the talus (AM-Ta), posterolateral part of the talus (PL-Ta), and posteromedial part of the talus (PM-Ta) ( Figure 1A).…”
Section: Quantitative Analysis Of the Mapping Imagesmentioning
confidence: 99%
“…According to the results of a previous study, the intraobserver and interobserver variations during CTOAM analysis were considered acceptable. 8…”
Section: Intraobserver Reliability and Interobserver Reproducibilitymentioning
confidence: 99%
“…Several studies reported excessive valgus stress on the elbow joint in pitching activity. 6,7,17 An important biomechanical study in pitching activity demonstrated that compressive forces measuring 500 N were observed in the radiocapitellar joint during the late cocking and early acceleration phases of throwing. 6 This excessive valgus stress may also reflect radial head enlargement and the skeletal age difference between the radial heads.…”
Section: Discussionmentioning
confidence: 99%